Being a Sub-Saharan Migrant: a Glance at the Italian Case in a Gender-Aware Perspective - Lapov, Zoran (Comparative Cultural Studies: European and Latin American Perspectives, 2017)
Resting on a gender-oriented approach, Zoran Lapov's text aims to retrace the migratory experiences of Sub-Saharan women taking them from their native lands to Europa, with a focus on the Italian case. Starting from the results of the international LeFamSol Project addressing Sub-Saharan migrant women in Italy, Greece and Turkey (2014-15), the present work is split into two parts: the first one, examining Africa-to-Europe migrations with particular attention to Sub-Saharan segments in Italy, is largely interested in push and pull factors underlying the phenomenon of Sub-Saharan female migrations, and in the most recent statistics on the topic; the second part, instead, sheds light on the mechanisms of inclusion, while delving into integration paths and strategies of Sub-Saharan African communities, esp. women, in Italy, and offering a panorama of their community organisation and social mobilisation (associations, networks, groups, etc.), including their specific needs and priorities. While treating the issue in terms of participatory processes in a gender-aware perspective, the paper has the ambition to contribute to the multilevel study and debate leading women, migrations and frontiers to meet.